Enhanced dimension-specific visual working memory in grapheme-color synesthesia. - Terhune, D; Wudarczyk, O; Kochuparampil, P; Cohen Kadosh, R (2013)
There is emerging evidence that the encoding of visual information and the maintenance of this information in a temporarily accessible state in working memory rely on the same neural mechanisms. A consequence of this overlap is that atypical forms of perception should influence working memory. We examined this by investigating whether having grapheme-color synesthesia, a condition characterized by the involuntary experience of color photisms when reading or representing graphemes, would confer benefits on working memory. Two competing hypotheses propose that superior memory in synesthesia results from information being coded in two information channels (dual-coding) or from superior dimension-specific visual processing (enhanced processing). We discriminated between these hypotheses in three n-back experiments in which controls and synesthetes viewed inducer and non-inducer graphemes and maintained color or grapheme information in working memory. Synesthetes displayed superior color working memory than controls for both grapheme types, whereas the two groups did not differ in grapheme working memory. Further analyses excluded the possibilities of enhanced working memory among synesthetes being due to greater color discrimination, stimulus color familiarity, or bidirectionality. These results reveal enhanced dimension-specific visual working memory in this population and supply further evidence for a close relationship between sensory processing and the maintenance of sensory information in working memory.